Pengendalian Persediaan Bahan Baku Aluminium Menggunakan Metode Continuous Review System dan Periodic Review System di PT. A - Maharani, Dita (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2023)
PT. A is an aluminum manufacturing company that uses Aluminum Ingot as the main raw material. Fluctuating demand causes accumulation and shortages in the warehouse. The purpose of this study is to determine and analyze the control of Aluminum Ingot inventory using the Continuous Review System and Periodic Review System methods in order to obtain a total inventory cost optimization strategy and ensure the continuity of the production process. Based on the 2022 inventory calculation, the Continuous Review System method is the best method that can reduce the total inventory cost by Rp15.871.580.630,35 or by 7,15% of the company's total inventory cost. The calculation of the total inventory cost for the period June 2023 - May 2024 obtained a result of Rp246,197,961,019.38 with an order quantity (q0) of 215 tons, a safety stock value (ss) of 25 tons, and a reorder point (r) of 90.8 tons.